The distal radial physis: Exploring normal anatomy on MRI enables interpretation of stress related changes in young gymnasts - Kraan, R. B. J.; Kox, L. S.; Oostra, R. J.; Kuijer, P. P. F. M.; Maas, M. (European Journal of Sport Science, 2020)
Rationale: Explore the MRI-appearance of the healthy distal radial physis and the distribution of stress-related changes in physeal thickness in young gymnasts to aid in the understanding of the pathophysiological process of stress-related physeal injury.